The Instability of High-Steep Road Cutting Slope: A 3D Continuum-Discrete Coupling Method. (24th June 2022) - Han, Dayong; Yang, Chao; Wang, Liang; Li, Dong; Liu, Yang
Abstract : In this paper, the 3D continuum-discrete coupling analysis method combined with the strength reduction theory is used to study the macrodeformation, stress law, and microfracture mechanism of a high and steep cutting slope of Zhongkai Expressway in Guangdong Province. The 3D continuum-discrete coupling slope model is established based on the finite difference software FLAC and the discrete element program PFC. Then, based on the correlations between stress tensor and force chain, displacement and shear strain increment, plastic deformation, and microfracture, the mechanism of slope instability is analyzed from macro- and microscales. The research shows the following: (1) the continuum-discrete coupling model is reasonable and effective in the three-dimensional slope stability analysis. (2) The coupling domain was penetrated by the shear band, and the upper part displacement of the coupling domain was large, whose direction was basically consistent with the shear band direction; thus, the slope slip surface was formed. (3) The microfracture can represent the macroscopic failure phenomenon, and the slope landslide can be interpreted as the result of shear fracture in slip direction, accompanied by the extension and penetration of tension crack.